Lipopolyplex potentiates anti-tumor immunity of mRNA-based vaccination - Persano, Stefano (Biomaterials, 2017)
mRNA-based vaccines have the benefit of triggering robust anti-cancer immunity without the potential danger of genome integration from DNA vaccines or the limitation of antigen selection from peptide vaccines. Yet, a conventional mRNA vaccine comprising of condensed mRNA molecules in a positively charged protein core structure is not effectively internalized by the antigen-presenting cells. It cannot offer sufficient protection for mRNA molecules from degradation by plasma and tissue enzymes either. Here, we have developed a lipopolyplex mRNA vaccine that consists of a poly-(β-amino ester) polymer mRNA core encapsulated into a 1,2-dioleoyl-sn-glycero-3-ethylphosphocholine/1,2-dioleoyl-sn-glycero-3-phosphatidyl-ethanolamine/1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polyethylene glycol)-2000 (EDOPC/DOPE/DSPE-PEG) lipid shell. This core-shell structured mRNA vaccine enters dendritic cells through macropinocytosis. It displayed intrinsic adjuvant activity by potently stimulating interferon-β and interleukin-12 expression in dendritic cells through Toll-like receptor 7/8 signaling. Dendritic cells treated with the mRNA vaccine displayed enhanced antigen presentation capability. Mice bearing lung metastatic B16-OVA tumors expressing the ovalbumin antigen were treated with the lipopolyplex mRNA, and over 90% reduction of tumor nodules was observed. Collectively, this core-shell structure offers a promising platform for mRNA vaccine development.